PEMANFAATAN MEDIA PEMBELAJARAN (GADGET) UNTUK MEMOTIVASI BELAJAR SISWA SD - Fifit Fitriansyah (Universitas Bina Sarana Informatika, 2016)
A teacher or instructor plays an important role in providing facilities tostudents to achieve the desired competency. So to increase the competence ofstudents, teachers or instructors should have an understanding of effectiveteaching methods, efficient and attractive to students. Along with the developmentof information and communication technology (ICT) in education, teacher orinstructor is expected to take advantage of the learning media that one of them byusing instructional gadget. With the use of gadget instructional, students becomemore interesting and learning become more varied and enjoyable.